Using museum pelt collections to generate pollen prints from high-risk regions: A new palynological forensic strategy for geolocation. (January 2020) - Warny, Sophie; Ferguson, Shannon; Hafner, Mark S.; Escarguel, Gilles
Highlights: The project focusses on the use of pollen in geolocation for trade compliance, criminal investigation and counter-terrorism endeavors. Geolocation based on pollen is possible because each plant has a pollen grain that is specific to it, and each pollen grain has a unique morphology. The problem is to generate prints from a region of interest to compare to pollen found on a suspect or items if these regions are no longer accessible. This manuscript describes an innovative approach to use historical museum collections to gather intelligence data from sensitive locations. It is a timely paper to showcase the significance of Museum collections in the context of homeland security. Abstract: The use of pollen as a forensic tool for geolocation is a well-established practice worldwide in cases ranging from the provenance of drugs and other illicit materials to tracking the travel of individuals in criminal investigations. Here we propose a novel approach to generation of pollen databases that uses pollen vacuumed from mammal pelts collected historically from international areas that are now deemed too high risk to visit. We present the results of a study we conducted using mammal pelts collected from Mexico. This new investigative technique is important because, although it would seem that the ubiquitous and geo-specific nature of pollen would make pollen analysis among the most promising forensic tools for law enforcement and intelligence agencies, it is not the case. The process is notoriously slow because pollen identification is a tedious task requiring trained specialists (palynologists) who are few in number worldwide, and the reference materials necessary for geolocation usually are rare or absent, especially from regions of the world that are no longer safe to visit because of war or threat of terrorism. Current forensic palynological work is carried out by a few highly trained palynologists who require accurate databases of pollen distribution, especially from sensitive areas, to do their jobs accurately and efficiently. Our project shows the suitability of using the untapped museum pelt resources to support homeland security programs. This first palynological study using museum pelts yielded 133 different pollen and spore types, including 8 moss or fern families, 12 gymnosperm genera and 112 angiosperm species. We show that the palynological print from each region is statistically different with some important clustering, demonstrating the potential to use this technique for geolocation.